“You Cannot Be Yourself”: Identity disruption, stigma, and the lived experience of anal fistula - Karin Adamo; Fredrik Brännström; Jeaneth Johansson; Karin Strigård (PLoS ONE, 2026)
Anal fistula is a complex and often prolonged condition that significantly impacts patients’ daily lives and psychological well-being. This qualitative study explored how individuals living with anal fistula experience stigma, disruption, and identity strain in everyday life. Fifteen participants undergoing active treatment were interviewed at two hospitals. Data was analyzed using qualitative content analysis. Findings show that living with anal fistula was marked by shame, uncertainty, and social withdrawal, often contributing to an altered or fractured sense of self. Participants navigated this experience through three identity-shaping mechanisms: Knowledge Uncertainty, Expectations and Experiences, and Quality-of-Life. These mechanisms influenced how participants made sense of their condition, coped with invisibility, and negotiated bodily control in the context of pain and stigma. While many struggled to maintain a coherent identity in the face of chronic symptoms, interactions with empathetic healthcare providers, particularly those offering consistent information and emotional support played a critical role in helping patients feel seen and supported. The study highlights the need for more holistic, person-centered approaches to care that address not only the physical but also the psychosocial dimensions of life with an anal fistula.